Investigating the effect of experiential marketing on intention to revisit healthcare and treatment organizations: A case study of clinics of the social security organization in Qom - Fatemeh Daei bidgoli; leila Nazarimanesh; Kamran Hajinabi (Tehran University of Medical Sciences, 2023)
Background and Purpose: Experiential marketing is a type of marketing strategy that attracts and engages customers by creating real-life experiences, allowing them to form lasting positive memories. Creating an excellent customer experience in the healthcare sector is challenging. Therefore, the aim of this study is to investigate the effect of experiential marketing on the intention to revisit social security clinics in Qom province. Methods: This quantitative and applied research utilized a survey approach for data collection. The statistical population comprised clients of the social security clinics in Qom province. A total of 522 individuals were invited to participate in the study using stratified random sampling. Data analysis was conducted using covariance-oriented structural equation modeling with the help of Amos V24 software. Results: The effect of experiential marketing (with dimensions of sensory experience, physical experience, emotional experience, cognitive experience, and relational experience) on the intention to return to the clinic was confirmed, with a path coefficient value of +0.540. Additionally, the structural indicators of the model and the validity of the constructs demonstrated a good fit for the model. Conclusion: Experiential marketing, along with the enhancement of patient-doctor relationships, is crucial. Patient-centered facilities can increase the likelihood of patients returning to clinics by focusing on experiential marketing, providing amenities, and utilizing technologies to improve service delivery.